STRUCTURAL AND SPECTRAL STUDIES OF THE MIXED-LIGAND CATION COMPLEX OF LANTHANUM [Lа(L)2bipy2]BPh4 WITH CARBACYLAMIDOPHOSPHATE (CAPh) TYPE LIGAND AND 2,2'-BIPYRIDINE: DOI: https://doi.org/10.17721/1728-2209.2020.1(57).4 (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2020)
A new cationic mixed-ligand complex [Lа(L)2bipy2]BPh4 (where L-= bis(N,N'-diethylamide)(N'-trichloroacetyl)-triamidophosphate anion, bipy = 2,2'-bipyridine) has been synthesized and studied by the means of IR, 1H NMR spectroscopy, thermogravimetric and X-ray structural analyses. Low-frequency shifts of the absorption bands of the carbonyl and phosphoryl groups of phosphorylated ligand in the IR spectra of the complex compared with similar absorption bands in the spectrum of "free" CAPh ligand are Δν(C = O) = 117 cm–1 and Δν(P = O) = 137 cm–1. The analysis of integral signal intensity in the investigated NMR spectra of coordination compounds [Lа(L)2bipy2]BPh4 indicates the molar ratio of ligand : bipyridine : tetraphenylborate anion as a 2:2:1, which corresponds to the proposed structure of the complexes. The compound has been obtained in monocrystalline form. The structure of the complex has been determined by X-ray structural analysis, its ionic structure was proved, and the coordination of two CAPh ligands through the oxygen atoms of the carbonyl and phosphoryl groups was confirmed. Based on the structural data, it was determined that the La3+ ion is octocoordinated (surrounded by four oxygen atoms from two chelated phosphoryl ligands and four nitrogen atoms from two 2,2'-bipyridine molecules). The coordination polyhedron of central ion is interpreted as a square antiprism. Complex cations and tetraphenylborate anions are connected both by electrostatic interaction and by weak intermolecular C – H ∙∙∙ π-contacts between phenyl substituents of BPh4- and molecules of 2,2'-bipyridine. It was established by thermogravimetric analysis that the complex [Lа(L)2bipy2]BPh4 obtained is thermally stable up to a temperature of 150 °C. Significant decomposition of the complex begins at a temperature of 150 °C, occurs in one stage and most intensively continues up to 300 °C. The total weight loss is 78 %.
Keywords: CAPh ligands, carbacylamidophosphates, lanthanum, mixed-ligand complexes, X-ray structural analysis.